Robotics engineering : learn it, try it! - Sobey, Edwin J. C., 1948- (North Mankato, Minn. : Dabble Lab/Capstone Press, a Capstone imprint, 2018)
An introduction to careers in robotics engineering and includes projects for practicing related skills.
Includes bibliographical references (p. 47) and index.
6.8
5-8
5-8
Keywords: Robotics -- Vocational guidance -- Juvenile literature; Engineering -- Vocational guidance -- Juvenile literature; Vocational guidance -- Juvenile literature; Robotics -- Vocational guidance; Engineering -- Vocational guidance; Vocational guidance; Engineering -- Vocational guidance; Vocational guidance; Robots -- Vocational guidance